Concept of Rasayana and its Role in Current Times-A Review - Sitpal, Nivedita; Pamnani, Gulab Chand; Agalcha, Rohan (International Research Journal of Ayurveda & Yoga, 2022)
Introduction: The word Rasayana means the way for attaining excellent Rasadi Dhatus. Rasayana is a unique branch of Ayurveda. It promotes the inner healing power of an individual and helps in over taking the pain and disease while promoting the immunity (Svasthasya Orjaskaram). As we know, in the present era, every human being is living under pressure to survive. This stressful life harms our health, happiness and inner sense of well-being. Increased pollution and excessive use of chemical products are also a root of many fatal diseases. In this regard, Rasayana Therapy becomes an essential tool to rejuvenate the body system for a better harmony in body, mind and soul. Advances in recent decades in understanding of aging have revived interest in antiaging factors and thus also in the Rasayana therapy. Rasayana Therapy is also known as Rejuvenation therapy which aims to restore the body’s vigour and vitality. In this review, concept of Rasayana and its role in the present era has been highlighted. Methods: The material has been collected from various Ayurveda texts and scholarly articles for deep understanding of Rasayana. Results: Rasayana is a specialized type of treatment influencing the fundamental aspects of the body viz. dhatus (body tissues), agni (the metabolic activity) and strotamsi (microcirculation) and helps in the prevention of aging. This review showed that Rasayana may provide age-stabilizing effects along with the preservation and promotion of health. Discussion: The purpose of Ayurveda is maintenance of Swasthya (health) and treatment of the Aatura (diseased person).Rasayana is equally important in treatment of diseases as well as in maintaining health. Use of different Rasayana herbs as per disease is useful in correcting Dhatu Vaishamya and attaining Dhatu Samya. Proper understanding and application of this concept in practice of Ayurveda would only lead to perfect and precise treatment.